2014
DOI: 10.1161/circinterventions.113.000653
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Contrast-Induced Nephropathy With N-Acetylcysteine or Sodium Bicarbonate in Patients With ST-Segment–Myocardial Infarction

Abstract: Background-Contrast-induced nephropathy (CIN) is a serious condition in patients with ST-segment-elevation myocardial infarction treated with primary percutaneous coronary intervention. We compared the risk of acute CIN and the influence of preventive strategies in patients with ST-segment-elevation myocardial infarction undergoing primary percutaneous coronary intervention. Methods and Results-A total of 720 patients were randomized in the Prevention of Contrast-induced Nephropathy inPatients With ST-Segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Guideline‐recommended strategies for the prevention of AKI include preventive hydration with isotonic saline and the minimization of the amount of contrast media . Efforts to further reduce the incidence of AKI have yielded mixed results and mainly included the use of N‐acetylcysteine and sodium bicarbonate, or the administration of statins or ascorbic acid . Our findings further strengthen the unmet clinical need for novel strategies to reduce the occurrence of AKI in high‐risk patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 54%
“…Guideline‐recommended strategies for the prevention of AKI include preventive hydration with isotonic saline and the minimization of the amount of contrast media . Efforts to further reduce the incidence of AKI have yielded mixed results and mainly included the use of N‐acetylcysteine and sodium bicarbonate, or the administration of statins or ascorbic acid . Our findings further strengthen the unmet clinical need for novel strategies to reduce the occurrence of AKI in high‐risk patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 54%
“…Twenty-three were first removed due to duplication. After initial review of the titles and abstracts of the left 33 studies, 3 studies 3335 comparing N-acetylcysteine (NAC) versus sodium bicarbonate and 1 study regarding hydration with SB pre- and postprocedurally while hydration with SC only postprocedurally were excluded. The remaining 19 studies were further screened into the full texts and 3 studies 36–38 were rejected because of low quality according to the Jadad score.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some previous reports revealed that hydration with sodium bicarbonate improved acidosis as the rapid increase of intravascular volume was more effective than hydration with sodium chloride for prophylaxis of CIN . In contrast, previous reports have shown that hydration with sodium bicarbonate had no clinical superiority in reducing the risk of CIN than that with sodium chloride . Since there is no evidence that hydration with sodium bicarbonate decreases the risk of hemodialysis or death, the effect of intervention for acidosis prevention may have a limited impact on CIN.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In contrast, previous reports have shown that hydration with sodium bicarbonate had no clinical superiority in reducing the risk of CIN than that with sodium chloride. [36][37][38][39] Since there is no evidence that hydration with sodium bicarbonate decreases the risk of hemodialysis or death, the effect of intervention for acidosis prevention may have a limited impact on CIN. Hence, now we conclude that acidosis is useful as a marker of risk stratification for CIN.…”
Section: Contrast-induced Nephropathymentioning
confidence: 99%